Integrating cognitive architectures into virtual character design - Turner, Jeremy Owen; Nixon, Michael 1981-; Bernardet, Ulysses 1969-; DiPaola, Steve (Advances in computational intelligence and robotics (ACIR) book series, 2016)
This book presents emerging research on virtual character artificial intelligence systems and procedures and the integration of cognitive architectures by emphasizing innovative methodologies for intelligent virtual character integration and design